2015
DOI: 10.1182/blood-2014-07-591040
|View full text |Cite
|
Sign up to set email alerts
|

P-Rex and Vav Rac-GEFs in platelets control leukocyte recruitment to sites of inflammation

Abstract: Key Points• P-Rex and Vav Rac-GEFs cooperate in leukocyte recruitment during inflammation by facilitating leukocyte adhesion to the vascular endothelium.• P-Rex/Vav expression in platelets is required for vascular adhesion and recruitment of neutrophils and eosinophils into lung tissue.The small GTPase Rac is required for neutrophil recruitment during inflammation, but its guanine-nucleotide exchange factor (GEF) activators seem dispensable for this process, which led us to investigate the possibility of coope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 52 publications
5
89
0
Order By: Relevance
“…Additional experiments have also revealed that the AngII-mediated stimulation of neutrophil migration and ROS production is Vav1 independent (Fabbiano, unpublished). These data are in agreement with previous results from the lab of H. Welch indicating no major defects in the in vivo biological properties of Vav1 Ϫ/Ϫ neutrophils (53,54). It would be important, in any case, to continue the analyses of Vav1 Ϫ/Ϫ T REG cells and neutrophils in order to assess whether this protein plays some catalysis-dependent or independent roles in any of these cell types.…”
Section: Our Results Have Unveiled a Hitherto Unknown Cd39supporting
confidence: 81%
“…Additional experiments have also revealed that the AngII-mediated stimulation of neutrophil migration and ROS production is Vav1 independent (Fabbiano, unpublished). These data are in agreement with previous results from the lab of H. Welch indicating no major defects in the in vivo biological properties of Vav1 Ϫ/Ϫ neutrophils (53,54). It would be important, in any case, to continue the analyses of Vav1 Ϫ/Ϫ T REG cells and neutrophils in order to assess whether this protein plays some catalysis-dependent or independent roles in any of these cell types.…”
Section: Our Results Have Unveiled a Hitherto Unknown Cd39supporting
confidence: 81%
“…70 We have also demonstrated that the Rac-GEF proteins P-Rex and Vav, which are essential for leukocyte (neutrophil) motility, are also present in platelets and central to the signaling required for platelet-dependent leukocyte recruitment. 71 These observations open up the distinct possibility of targeting such signaling mechanisms as novel approaches for the development of anti-inflammatory drugs.…”
Section: Dichotomy Of Platelet Activation and Future Perspectives Formentioning
confidence: 99%
“…Although Vav GEFs alone are largely dispensable for neutrophil recruitment, they do cooperate with P‐Rex1 to regulate neutrophil adhesion, migration and tissue recruitment . Prex1 −/− Vav1 −/− neutrophils show reduced cell surface levels of LFA‐1 and Mac‐1 and have more profound defects in fMLP‐stimulated Rac1 and Rac2 activity, adhesion and migration than neutrophils which lack either the P‐Rex or Vav families . Similarly, neutrophil recruitment during sterile peritonitis is more severely impaired in Prex1 −/− Vav1 −/− or Prex1 −/− Vav3 −/− mice than in strains that lack either GEF family .…”
Section: Rac‐gefs In Neutrophil Adhesion Migration and Recruitmentmentioning
confidence: 99%